Use of Zebrafish Embryos for Small Molecule Screening Related to Cancer. Issue 2 (22nd January 2013) - Terriente, Javier; Pujades, Cristina
<x xml:space="preserve">Abstract</x> The introduction of mechanism‐based targeted therapies to treat human cancers is fruit of decades of research into the molecular basis of cancer pathogenesis. Despite the growing knowledge about the molecular mechanisms governing its causes and progression, there is a lack of effective treatments for many types of cancer. The expensive and time‐consuming preclinical pipeline for testing molecules slows the discovery of new therapies. Therefore, it is important to consider alternative methodologies both for accelerating therapeutic discovery and reducing costs. In that regard, zebrafish is becoming an attractive model for fast and efficient drug screening. Its use has expanded to many disease research areas, and the postgenomic era has led to the progression of functional studies and boosted the development of general databases, such as ZFIN, and the emergence of more specialized ones, including several catalogues of transgenic reporter screens. Taken together, they provide to the scientific community many tools that could be used for drug discovery. The use of zebrafish in cancer drug screenings could help to economize time and resources even more if we rationalize its use: we could use embryonic screens to identify drugs that address general hallmarks of cancer, and use adults for finding molecules that target specific cancer models. Developmental Dynamics 242:97–107, 2013. © 2012 Wiley Periodicals, Inc.